Implikasi Standar Sertifikasi Halal Internasional terhadap Perdagangan Global Indonesia pada Produk Halal - Naila Naila; Risma Risma; Diana Putri Utari; Anabilla Alma Widyaningtias; Lina Marlina (Institut Teknologi dan Bisnis (ITB) Semarang, 2025)
This study analyzes the implications of international halal certification standards on the global trade of Indonesian halal products. The focus of the study covers the impact of standard harmonization, particularly through the OIC/SMIIC, on increasing export market access and the competitiveness of Indonesian products. The method used is a qualitative approach with descriptive-comparative analysis based on national regulations, BPJPH documents, and international standards. The results of the study show that the application of international halal standards strengthens global consumer confidence and opens up wider export opportunities for Indonesian products. However, differences in regulations between countries, high certification costs, and limited capacity of halal institutions remain major obstacles. Standard harmonization and strengthening of national certification institutions are needed so that Indonesia can optimally utilize the potential of the global halal market.